Tuberculosis and hospitalization incidence postpartum among women living with HIV in Gugulethu, Western Cape, South Africa - Njoku, Kelechi Francisca (Department of Public Health and Family Medicine, 2020)
Background: Knowledge of the incidence of tuberculosis (TB) and hospitalization postpartum could reduce maternal morbidity and mortality. TB infections are prevalent in pregnant women living with Human immunodeficiency virus (HIV) compared to women not living with HIV in South Africa. Adherence to Antiretroviral Therapy (ART) is poor among pregnant and postpartum women living with HIV (WLHIV), thus making WLHIV at a higher risk of hospitalization postpartum, due to the increased risk of Cesarean delivery (CD) and obstetric conditions as a result of HIV. The prevalence of TB among pregnant and postpartum women is poorly defined including in high prevalence TB and HIV locations, indicating limited evidence. The aim is to explore the incidence of TB and hospitalization within four years postpartum among WLHIV, including associated risk factors. Methodology: The study population is from phase 2 of the Maternal and Child HealthAntiretroviral Therapy (MCH-ART) study. It is a single-arm observational cohort study of 628 WLHIV who attended antenatal care (ANC). Enrolment into phase 1 began in March 2013, the final deliveries from phase 2 were in December 2014, and the final follow-up visits were completed in 2016. MCH-ART is an ongoing study with global approval examining strategies for providing HIV care and treatment to HIV-infected women who initiate ART during pregnancy and their HIV-exposed infants. This study took place at the Midwife-Obstetric Unit (MOU) at Gugulethu Community Health Centre, Western Cape South Africa. It consists of three connected study designs and three phases through the antenatal and postnatal periods. Phase 1 is a cross-sectional study, phase 2 is a cohort study and phase 3 is a randomized trial. Kaplan-Meier survival analysis was used to assess the incidence of TB and hospitalization over time among ix WLHIV up to four years postpartum and Cox regression was used to measure the effect of risk factors on the incidence of TB and hospitalization. Results: Thirty-five (35) WLHIV developed TB postpartum at a total person-time of 2365.1 woman-years. The incidence rate (IR) of developing TB among WLHIV postpartum was 1.48 (95% CI=1.03-2.06) cases per 100 woman-years from 2013 to 2018. Twenty-three (23) WLHIV was hospitalized postpartum and a total person-time of 552.8 woman-years was spent. The IR of hospitalization among WLHIV postpartum was 4.16 (95% CI=2.64-6.24) cases per 100 womanyears from 2013 to 2018. The IR of TB and hospitalization among WLHIV postpartum is statistically significant. Adjusting, for other risk factors, the history of diabetes at ANC, the history of TB at ANC and CD4 count (200 - <500) cells/mm3 at ANC also significantly increases the incidence of TB postpartum, whereas, obstetric reasons is associated with the hospitalization of WLHIV.